Presentation Knowledge in the Americas: Crossroads, Trajectories, and Trading Zones [Presentación Saberes en Las Américas: Cruces, Trayectorias y Zonas de Intercambio] - Labarca-Pinto, M (Universidade Federal de Minas Gerais, 2022)
[No abstract available]